MANAJEMEN PENGUPAHAN PADA CV. ANATO GROUP KELURAHAN DATA KABUPATEN PINRANG (DITINJAU DARI PERSPEKTIF AKUNTANSI SYARIAH) - As, Erwin Irnandi; Herman, Bahtiar; Cahyani Tahir, Inna Mutmainna (Universitas Ichsan Sidenreng Rappang, 2025)
The issue of discrepancies between wages determined by companies and the actual needs of workers often leads to dissatisfaction toward both employers and the government. Wages are vital for workers’ daily lives, making the fulfillment of labor rights, especially in terms of remuneration, a crucial matter. This study aims to analyze the wage management system at CV. Anato Group, Kelurahan Data, Pinrang Regency, and to examine it from the perspective of Sharia accounting. The research applies a descriptive qualitative approach through field research. Primary data were collected through direct observation and interviews at CV. Anato Group, while secondary data were obtained from books, library resources, and online sources. Data collection techniques included observation, interviews, and documentation. The findings indicate that wage management at CV. Anato Group is implemented through the stages of planning, organizing, directing, and controlling, and has been carried out effectively. The wage system is calculated based on the number of working days and paid monthly according to employee attendance. This mechanism was agreed upon in advance between the company and its workers. From the perspective of Sharia accounting, the wage system applied by CV. Anato Group complies with principles of fairness, trust, and transparency. Workers perform their duties responsibly, while the company maintains clear and mutually agreed-upon records of income and expenses. Wages are provided fairly, appropriately, and on time, and compensation is aligned with the actual hours worked. Thus, wage management at CV. Anato Group not only meets technical management aspects but also reflects Sharia values that emphasize justice and openness.